O futuro do trabalho: impactos e desafios para as organizações em Angola - Baptista, Jorge Cabral (2016)
The future of work today has become a concern not only for scholars in the field, but also for society in general, taking into account the changes recorded both in business environment as social because of the profound changes that we know today. However, they are now experiencing new ways to do their work, changes in the professional profile of the people and in relations with organizations, providing challenges, in particular adaptations to these changes. This thesis has as its primary goal, the understanding of how the progress of work in the world has affected the Angolan organizations, what are the challenges and implications they face, especially in relations with professionals. The theoretical framework was based on literature that portrays the subject under study, a current topic of interest to the various areas of knowledge such as sociology, economics, organizational studies, anthropology and others, which allowed the understanding of how the labor market reacts these changes face the changes that are imposed. The kind of adopted research was descriptive and exploratory a qualitative approach. For data collection was used the survey method with the application of 181 questionnaires addressed to managers of Angolan companies and the data were treated from the descriptive statistical technique (absolute frequency, relative frequency, mean, median and mode). To analyze the data, we raised three dimensions arising from the theoretical and empirical data that enabled the discussion of the data. The research concludes that although Angola is experiencing an economy in recession, the impact and challenge of the future of work can bring several changes in emphasis to labor market for flexible working conditions, the emergence of new models of management and likely social changes that could lead to the reduction of formal work and provide flexible contracts.